Introducing Standardized Assessment and Management of Oral Cares in a Rehabilitation Unit: Patient Outcomes and Experiences. Issue 5 (11th September 2021) - Schwarz, Maria; Kwiecien, Inger; Hamlet, Blaise; Coccetti, Anne; Monsiegneur, Ursula; Tickle, Benjamin; Cardell, Elizabeth
Abstract: Purpose: The aim of this study was to improve patient oral hygiene outcomes in a rehabilitation unit by implementing a nursing education package and oral hygiene assessment tool. Design: A case–control design with 50 rehabilitation patients was performed. Methods: Nursing staff received education and training in applying the Modified Oral Health Assessment Tool. Clinician assessment of patient oral hygiene occurred on admission and at days 5–7. Each patient reported their perceptions of oral hygiene and comfort prior to hospitalization, while in the hospital, and after transfer to the rehabilitation unit. Findings: Oral hygiene rating scores improved significantly from admission to the rehabilitation unit to days 5–7 ( p = .00). The mean score of patient perceived cleanliness improved from hospital admission to admission to the rehabilitation unit. Conclusion: Oral hygiene was improved following admission to a rehabilitation unit with a consistent and individualized approach to oral hygiene. Clinical Relevance: The introduction of a consistent and individualized approach to oral hygiene demonstrates positive patient outcomes and high patient acceptance.